Personal Tempo for students of university - Mansour Hussin , Rudhab; Saad Khair Allah, Thuraya (Journal of College of Education, 2020)
Personal tempo and its relation to the efficiency of the cognitive representation of university students .Current search goal to know:1. The level of personal rhythm among university students2. Differences in the level of personal rhythm by variable Gender, specialization, stage .   To achieve the objectives of the current research, the researcher used the Kaufman battery and selected four tests to measure the personal rhythm of the university students. The researcher built the efficiency of cognitive representation and applied the battery and the scale to the sample of statistical analysis (300) students.1.University students enjoy a normal level of personal rhythm.2. To find statistical differences in the level of personal rhythm by sex variable (males, females) it was found that there are statistically significant differences between male and female students in the level of personal rhythm in favor of female students .    In the light of the conclusions reached, the researcher recommended a set of recommendations and proposals